Stability Analysis of a Fractional Order Discrete Anti-Periodic Boundary Value Problem - Selvam, A. George Maria; Jacintha, Mary; Dhineshbabu, R. (Communications in Mathematics and Applications, 2021)
This article aims at investigating stability properties for a class of discrete fractional equations with anti-periodic boundary conditions of fractional order \(δ=(3,4]\). Utilizing Contraction mapping principle and fixed point theorem due to Brouwer, new criteria for the uniqueness and existence of the solutions are developed and two types of Ulam stability are analysed. The theoretical outcomes are corroborated with examples.
Keywords: Existence; Ulam Stability; Boundary Value Problem; Caputo Fractional Difference operator